1969
DOI: 10.1071/bi9691497
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Resistance to Boophilus Microplus, Nutritional Status, and Blood Composition in Shorthorn X Hereford Cattle

Abstract: SummaryRelationships between nutrition, blood composition, and tick resistance were studied in three groups of six yearling Shorthorn X Hereford steers. Feeding was ad libitum and group I was offered lucerne hay and safflower seeds, group II lucerne hay only, and group III wheat straw supplemented with molasses. All animals were infested five times with 0·5 g tick larvae during the treatment period of 62 days.The mean number of mature female ticks counted on one side of each animal and the mean percentage chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

1970
1970
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 19 publications
2
12
0
1
Order By: Relevance
“…Almost identical tick counts were produced by 9 g and 28 g of tick larvae on the animals fed low-and high-quality diets respectively. Thus, the percentage yield of mature ticks was about three times greater on low-quality than on highquality feed, suggesting a marked effect of nutrition on resistance and agreeing with previous findings (O'Kelly and Seifert 1969). However, the two experiments were carried out at different times of the year and the possibility of seasonal variation in tick resistance must be considered.…”
Section: (0) Conclusionsupporting
confidence: 90%
See 2 more Smart Citations
“…Almost identical tick counts were produced by 9 g and 28 g of tick larvae on the animals fed low-and high-quality diets respectively. Thus, the percentage yield of mature ticks was about three times greater on low-quality than on highquality feed, suggesting a marked effect of nutrition on resistance and agreeing with previous findings (O'Kelly and Seifert 1969). However, the two experiments were carried out at different times of the year and the possibility of seasonal variation in tick resistance must be considered.…”
Section: (0) Conclusionsupporting
confidence: 90%
“…A previous study (O'Kelly and Seifert 1969) showed weight gains and significant increases in haematocrit in lightly infested Shorthorn X Hereford steers on highquality diets. This investigation demonstrates that even an adequate diet cannot counterbalance the depression in growth rate and certain blood parameters caused by heavy tick burdens.…”
Section: (B) Experiments 2: Steers On High-quality Feedmentioning
confidence: 84%
See 1 more Smart Citation
“…In addition to obtaining nutritional benefits, oxpeckers use their hosts as mobile perches and sources of nesting material. Ungulates, in turn, reap the benefits of ectoparasite removal by associated oxpeckers, which includes the prevention of blood loss, appetite suppression, tick toxicosis, and skin, bacterial and protozoan diseases (Little, ; O'kelly & Seifert, ; Seebeck, Spingell & O'kelly, ; Williams, Hair & Mcnew, ; Price, ; Mulilo, ; Norval et al ., ; Hart, Hart & Mooring, ; Oorebeek & Kleindorfer, ). Because of this cleaning behaviour, the oxpecker–ungulate interaction is generally categorized as mutualistic, an interspecific interaction in which each species receives a net benefit (Bronstein, ,b, , ; Holland & Deangelis, ).…”
Section: Introductionmentioning
confidence: 99%
“…The same effect might be produced by tick infestation in cattle. O'Kelly and Seifert (1969) showed that blood phospholipid decreased during tick infestation when the level of nutrition was below maintenance. Phospholipase A is one of the two enzyme components of bee venom which are antigenic (Habermann 1972).…”
Section: Discussionmentioning
confidence: 99%